Developments in the Case Law of the EU Courts in Competition Law in 2016 - Catarina Vieira Peres (Market and Competition Law Review)
In this report we intend to briefly describe some of the most relevant cases of the General Court and the Court of Justice adopted during 2016 in Competition Law. During this year, there have been many interesting developments in what concerns both Article 101 of the Treaty on the Functioning of the European Union and State aids. There haven't been many cases on mergers or Article 102 TFEU, where the Court of Justice's decision in Intel's case is still awaited.